2013
DOI: 10.2478/s13545-013-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pattern prevails over spatial variability in phytoplankton communities from a subtropical water supply reservoir

Abstract: Phytoplankton species are dominant components in reservoir ecosystems, yet little is known about their variability and dynamics, especially along the depth continuum. This study examined vertical and horizontal differences in phytoplankton communities in a typical subtropical deep reservoir (i.e. Dongzhen Reservoir) from 2011 to 2012. Phytoplankton communities separated into four groups based on the biomass data, indicating that temporal differences in the community structure were greater than spatial differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…WT, TN, and Chla were significant factors affecting the community distribution of planktonic eukaryotes in 2018. The results showed that the community structure of planktonic eukaryotes changed significantly with temporal and spatial changes; the temporal changes caused corresponding changes in WT, DO, and other physical and chemical factors in the reservoir area and led to corresponding changes in the community structure and diversity of the planktonic eukaryotes [61]. The change in the central node between the single-factor and two-factor network analysis also illustrates this point.…”
Section: Changes In Planktonic Eukaryotic Community Structurementioning
confidence: 70%
“…WT, TN, and Chla were significant factors affecting the community distribution of planktonic eukaryotes in 2018. The results showed that the community structure of planktonic eukaryotes changed significantly with temporal and spatial changes; the temporal changes caused corresponding changes in WT, DO, and other physical and chemical factors in the reservoir area and led to corresponding changes in the community structure and diversity of the planktonic eukaryotes [61]. The change in the central node between the single-factor and two-factor network analysis also illustrates this point.…”
Section: Changes In Planktonic Eukaryotic Community Structurementioning
confidence: 70%
“…Several physical, chemical, and biological variables are known to influence the microbial community composition1112. Previous studies showed that the vertical dynamics of the phytoplankton was related to the water column-mixing regime13.…”
mentioning
confidence: 99%
“…Reservoirs are artificial multi-functional aquatic ecosystems that provide various ecosystem services for social development (e.g., economic, regulation, and cultural values) and represent an important water resource guarantee for social sustainable development [1,2]. China has more reservoirs than any other country, with dams built on almost all major and minor rivers except for Nujiang and Yarlung Zangbo, totaling more than 98,000 [3]. With the growth of the population and the increasing demand for water, the functions of these reservoirs have changed.…”
Section: Introductionmentioning
confidence: 99%